First, I will assume that the -3 at the beginning will not be raised to the -5th power.
A little revision of the law of indices is in order:
(ab)^n = a^n . b^n
this will apply to the ^4 and ^3 outside of the parentheses.
a^-n=1/a^n
This will apply to the term a^-5
b^0 = 1
for all values of b except 0.
(-3a^-5 b^6)^4 (a^7b^0)^3
=(-3b^6/a^5)^4 (a^7 . 1)^3
=(-3)^4 (b^6)^4 /(a^5)^4 (a^7)^3
= (-3)^4 (b^24)/(a^20) (a^21)
= ...
I will let you take it from here.
Post your answer for a check if you wish.
=
Help please....Please Simplify
(-3a^-5 b^6)^4 (a^7b^0)^3
any ideas? thanks in advance!
3 answers
Ok thanks! I got 81ab^24 Is this correct? Thanks!
Excellent, the answer is correct.
Do start the problem over to understand every step.
Do start the problem over to understand every step.